Application of Gross Tissue Response System in Gastric Cancer After Neoadjuvant Chemotherapy: A Primary Report of a Prospective Cohort Study - Yang, Hua; Zhang, Wei-Han; Ge, Rui; Peng, Bo-Qiang; Chen, Xin-Zu; Yang, Kun; Liu, Kai; Chen, Xiao-Long; He, Du; Liu, Jian-Ping; Zhang, Wei-Wei; Qin, Yun; et al. (Frontiers in Oncology, 2021)
Objective: We previously have established the gross tissue response (GTR) system to evaluate the intraoperative peri-gastric tissue response after neoadjuvant chemotherapy of gastric cancers. This prospective cohort study aims to confirm the relationship between gross tissue response and clinicopathological characteristics and explore the possibility of using GTR system to predict the difficulty of surgical operation and the occurrence of postoperative 30-day complications. Methods: A total of 102 gastric cancer cases from January 2019 to April 2020 were enrolled in the study. The fibrosis, edema, and effusion degree of peri-gastric tissues was intraoperative assessed according to the GTR system. We systematically analyzed relations among the GTR system and clinicopathological characteristics, then a prediction model including GTR was established to predict the difficulty of surgical operation and the occurrence of postoperative 30-day complications. Results: Finally, the study had included 71 males and 31 female patients. The average age of patients was 58.79 ± 1.03 years, BMI was 22.89 ±0.29, tumor diameter was 4.50±0.27 cm. Among these patients, 17 patients underwent laparoscopic gastrectomy, 85 patients underwent open gastrectomy, the average operation time was 294.63±4.84 minutes, and mean intraoperative blood loss was 94.65±5.30 ml. The overall incidence rate of postoperative 30-day complications was 19.6% (20/102). Total score of the GTR system was significantly related to the primary tumor stage of patients, operation time and postoperative 30-day complications(p<0.05). Edema, effusion was significantly related to intraoperative blood loss (p<0.05). The logistic regression analysis identified that the total score of the GTR system (score: 4-9, OR 2.888, 95% CI: 1.035-8.062, p = 0.043) was the independent risk factors for the postoperative 30-day complications, and the total score of the GTR system(score 4-9, OR 3.32, 95% CI 1.219-9.045, p=0.019) was the independent risk factor for the operation time concurrently. The AUC of total score of GTR system in the prediction of the postoperative 30-day complications was 0.690. Conclusion: According to the results of the present study, the gross Tissue response system (GTRs) is an effective indicator, which may be used in the prediction of incidence risk for the difficulty of operation after neo-chemotherapy and postoperative complications.